Gastric volvulus in the mediastinum through a hiatal hernia - Sarah Ellul; Gabriella Grech; Thomas Borg Barthet; Andre Stefan Gatt; Julie Galea; Mohamed Shoukry (Elsevier, 2022)
Introduction: Hiatal hernia (HH) is gastric herniation through the oesophageal hiatus into posterior mediastinum.We present an uncommon case of congenital sliding HH in healthy child, with organo-axial gastric-volvulus and normal mid-gut rotation. Case description: A 3-month-old female, presented with worsening coffee-ground vomiting for the last 6 weeks. Medical history was unremarkable. She was severely dehydrated with a soft abdomen and no obvious abdominal masses. Initial blood tests revealed elevated White Cell Count (WCC) mainly neutrophils, C-Reactive Protein (CRP) and lactate levels with normal electrolytes.CXR reported discontinuity of left hemi-diaphragm with the stomach shadow occupying the left lower hemi-thorax. The upper GI contrast study and chest CT-scan revealed stomach, pylorus and liver lobe wholly located in the chest, occupying the posterior mediastinum. Both sides of the hemi-thorax were clear, with no evidence of mid-gut malrotation. Radiological images confirmed presence of a large defect in posterior diaphragm around the midline, with stomach and liver herniating into the chest. Following resuscitation, nasogastric tube insertion and consent, a laparotomy revealed organo-axial volvulus of stomach and incarceration, along with the presence of a complete sliding HH through a large defect. Complete reduction of herniated contents, fundoplication and primary closure of defect undertaken. Uneventful post-operative recovery and discharged from hospital after 10 days. Conclusion: We present an infant with complete sliding HH complicated with organo-axial gastric volvulus. Such cases although rare, require high suspicion and prompt management in view of gastric volvulus, as mortality is considerable. With prompt evaluation and adequate resuscitation, we were able to provide immediate optimal surgical treatment and avoid unnecessary complications.